REPRESENTATIVE INFERENCE AND ITS IMPACT ON THE ARGUMENTATIVE POETS OF BUDAIYA - Nadhim Daas Awwad Al- Shaabani; Rumid Matar Hamad Al- Dulaimi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The purpose of this research is to identify the patterns of representative inference and its arguing effect on the Budaiya poets, and what this type of reasoning represents in drawing the attention of the recipient and convincing him of what the creator intends to convey to him, and that is by citing representative arguments; Because the inference is the affirmation or denial of the ruling, and this is only possible in the presence of evidence to prove that matter; Because representation is a mental mechanism on which the creator relies in producing his speech and delivering it to the recipient in the required image, as it requires from the creator an increase in awareness and awareness to highlight what raises the recipient astonishment and breaks the horizon of expectation. It also requires the recipient to increase discernment and good forethought; Therefore, it is necessary to highlight the artistic and literary value of this type of inference. The research consisted of an introduction and a topic in which I studied (the level of representational inference and its arguing effect on the Budaiya poets).